Multi-component cement-based repairing material and preparation method thereof
By using multi-component cement-based repair materials, combined with the ratio and stirring processes of silicate cement, fly ash, sulfoaluminate cement, glue powder and polypropylene fiber, traditional cement-based repair materials are solved by solving the cracking and resistance of traditional cement-based repair materials. The problem of poor permeability has achieved early strength improvement, cracking and permeability improvement, and settling time shortened.
Patent Information
- Application Number
- CN202411382661.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional silicate cement-based repair materials have disadvantages such as easy cracking, poor anti-chlorine ion penetration performance, long settling time, poor bonding strength, low flexural strength and carbon emissions, resulting in increased construction difficulty, long construction period, and repair Poor results.
Using multi-component cement-based repair materials, including silicate cement, fly ash, sulfur aluminate cement, glue powder and polypropylene fiber, slow stirring by uniform premix and slowly adding tap water with superplasticizer. and quick stirring to form efficient repair materials.
This material can repair microcracks of existing structures, improve early strength, compactness, crack resistance and permeability, reduce settling time, improve comprehensive performance, and extend service life.
Smart Images

Figure CN119430819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based materials, and in particular to a multi-component cement-based repair material and a preparation method thereof. Background Art
[0002] With the progress of human society and the development of technology, a large number of housing and transportation construction have been driven. In the 21st century, cement-based materials, as the most used building materials in the world, have many excellent properties and are widely used in various human infrastructure. However, due to the lack of understanding of material properties and loose construction supervision in the early stage, a large number of cement concrete structures have suffered varying degrees of damage and cracking, which seriously affected their service performance, posing great safety hazards to public safety and social production, and causing serious waste of resources.
[0003] Traditional silicate cement-based repair materials have the disadvantages of easy cracking, poor resistance to chloride ion penetration, long setting time, poor bonding strength, low flexural strength, and high carbon emissions, which increase the difficulty of construction operations, prolong the construction period, and have poor repair effects.
[0004] In order to improve the comprehensive performance of cement-based materials and extend their service life, a multi-component cement-based repair material and a preparation method thereof are provided. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a multi-component cement-based repair material, which comprises silicate cement, fly ash, sulphoaluminate cement, rubber powder and polypropylene fiber components, and can repair microcracks in existing structures, improve the early strength, density, crack resistance and impermeability of cement-based repair materials, and can reduce the setting time of cement-based repair materials, thereby improving the comprehensive performance of cement-based repair materials as a whole and extending their service life.
[0006] The invention also provides a method for preparing a multi-component cement-based repair material, which has simple steps, is easy to use, and is energy-saving and environmentally friendly.
[0007] The present invention solves the technical problem by the following technical solutions:
[0008] A multi-component cement-based repair material comprises the following components by mass percentage: silicate cement, fly ash content 0% to 30%, sulphoaluminate cement content 5% to 50%, rubber powder content 1% to 2.5%, polypropylene fiber content 0.1% to 0.25%; the benchmark mix ratio of the test piece is: cement: water: sand = 1:0.5:1.
[0009] Furthermore, the silicate cement is P·O42.5 silicate cement.
[0010] Furthermore, the fly ash has an average particle size of 80 μm and comprises the following components by mass percentage: CaO 6.80%, SiO 2 46.50%, Al 2 O 3 33.80%, Fe 2 O 3 9.80%, MgO 0.70%, SO 3 0.80%, K 2 O0.60%, Na 2 O0.10%, LOI0.90%.
[0011] Furthermore, the tensile strength of the polypropylene fiber is 385 MPa, the length range is 6 mm to 12 mm, and the elastic modulus is 5.8 GPa.
[0012] Furthermore, the sulphoaluminate cement is SAC42.5 rapid hardening sulphoaluminate with a 1d strength of 31 MPa and a 3d strength of 45.5 MPa.
[0013] Furthermore, the rubber powder is a dispersible or soluble rubber powder, the composition of which is ethylene-vinyl acetate polymer (EVA), the glass transition temperature is 15°C, and the bulk density is 550kg / m 3 , fineness 160μm.
[0014] Furthermore, the sand is river sand with a fineness modulus of 2.1.
[0015] A method for preparing a multi-component cement-based repair material as claimed in claim 1, comprising putting silicate cement, fly ash, sulphoaluminate cement, rubber powder and polypropylene fiber weighed according to a proportion into a mortar mixing pot, and premixing them uniformly for 60 seconds, then slowly adding tap water mixed with a superplasticizer into the mixing pot, stirring slowly for 60 seconds, stirring quickly for 90 seconds, and then stirring slowly for 60 seconds, and shoveling and mixing with a spatula, and performing a material performance test on the repair material after stirring, and repairing the test piece.
[0016] The advantages and positive effects of the present invention are:
[0017] The present invention discloses a multi-component cement-based repair material, which uses silicate cement and fly ash as main repair materials, and can repair micro cracks in existing structures to a certain extent; polypropylene fiber can improve its crack resistance; on this basis, soluble rubber powder and epoxy resin are introduced to further improve the anti-seepage performance of the repair material. At the same time, sulfoaluminate cement and accelerator greatly reduce the setting time of cement-based materials, so that the comprehensive performance of defective structures can be quickly improved in a relatively short time. Adding silica ash to the silicate cement-based repair material improves the early strength and density of the repair material. The present invention discloses a method for preparing a multi-component cement-based repair material, which has simple steps, is easy to use, and is energy-saving and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a test diagram of the effect of fly ash on electrical flux;
[0019] Figure 2 This is a test chart of the effect of sulphoaluminate cement on the setting time of the system;
[0020] Figure 3 This is a test chart showing the effect of the amount of rubber powder on the bonding strength of the specimen;
[0021] Figure 4 This is the test diagram of the effect of polypropylene fiber length 3mm on the strength of the specimen;
[0022] Figure 5 This is the test diagram of the effect of polypropylene fiber length 6mm on the strength of the specimen;
[0023] Figure 6 This is the test diagram of the effect of polypropylene fiber length 9mm on the strength of the specimen; DETAILED DESCRIPTION
[0024] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0025] A multi-component cement-based repair material comprises the following components by mass percentage: silicate cement, fly ash content 0% to 30%, sulphoaluminate cement content 5% to 50%, rubber powder content 1% to 2.5%, polypropylene fiber content 0.1% to 0.25%; the benchmark mix ratio of the test piece is: cement: water: sand = 1:0.5:1.
[0026] The silicate cement is P·O42.5 silicate cement.
[0027] The fly ash has an average particle size of 80 μm and comprises the following components by mass percentage: CaO 6.80%, SiO 2 46.50%, Al 2O 3 33.80%, Fe 2 O 3 9.80%, MgO 0.70%, SO 3 0.80%, K 2 O0.60%, Na 2 O0.10%, LOI0.90%.
[0028] Table 1 shows the chemical composition of fly ash:
[0029] Table 1 Chemical composition of fly ash (%)
[0030] Element CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> MgO <![CDATA[SO 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> LOI content 6.80% 46.50% 33.80% 9.80% 0.70% 0.80% 0.60% 0.10% 0.90%
[0031] The tensile strength of the polypropylene fiber is 385 MPa, the length range is 6 mm to 12 mm, and the elastic modulus is 5.8 GPa.
[0032] The sulphoaluminate cement is SAC42.5 rapid hardening sulphoaluminate with a 1d strength of 31 MPa and a 3d strength of 45.5 MPa.
[0033] The rubber powder is a dispersible or soluble rubber powder, and its composition is ethylene-vinyl acetate polymer (EVA), with a glass transition temperature of 15°C and a bulk density of 550kg / m 3 , fineness 160μm.
[0034] The sand is river sand with a fineness modulus of 2.1.
[0035] A preparation method of a multi-component cement-based repair material comprises the following steps: putting silicate cement, fly ash, sulphoaluminate cement, rubber powder and polypropylene fiber weighed in proportion into a mortar mixing pot, premixing them uniformly for 60 seconds, then slowly adding tap water mixed with a superplasticizer into the mixing pot, stirring them slowly for 60 seconds, stirring them quickly for 90 seconds, stirring them slowly for 60 seconds, and then stirring them slowly with a spatula. The repair material after stirring is tested for material properties, and a test piece is repaired.
[0036] During the test, the fly ash content was 0%, 5%, 10%, 15%, 20%, 30%; the sulphoaluminate cement (SAC) content was 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%; the rubber powder content was 1%, 1.5%, 2%, 2.5%; the polypropylene fiber content was 0.1%, 0.15%, 0.2%, 0.25%. The benchmark mix ratio of the specimen is cement: water: sand = 1: 0.5: 1.
[0037] Anti-penetration performance test:
[0038] The electric flux method was used to test the anti-penetration performance of the repair material in accordance with the standard "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009)".
[0039] The physical and chemical effects of fly ash can effectively improve the anti-permeability performance of cement-based materials. Here, different amounts of fly ash are added to the base mix in order to improve the anti-permeability performance of the repair material. The test results are as follows: Figure 1 shown.
[0040] from Figure 1 It can be seen that with the gradual increase of fly ash content, the electric flux of the specimen shows a pattern of first decreasing and then slightly increasing. When the fly ash content is 15%, the electric flux value of the specimen is relatively small. Compared with the benchmark specimen (fly ash content 0%), the electric flux value has decreased by about 34%. From the perspective of the electric flux value, when the electric flux value is in the range of 2000-3000, the chloride ion permeability of the specimen is "medium", and when the fly ash content is in the range of 15%-30%, the chloride ion permeability of the specimen belongs to the "bottom" level, which has good anti-permeability performance. When fly ash is added to the specimen, the micro-aggregate effect of fly ash can optimize the particle size distribution of the system and compact the system structure; its morphological effect can improve the fluidity of the new system; at the same time, the secondary hydration of fly ash generates a low-alkalinity gel with a relatively large specific surface area, which can adsorb chloride ions and generate "F" salt to consume chloride ions. The synergistic effect of the above aspects enhances the specimen's resistance to chloride ion penetration.
[0041] Setting time characteristic test:
[0042] The setting time of the repair material is tested with reference to the "Concrete Strength Test and Assessment Standard (GB50107-2010)".
[0043] Repair materials are required to have good setting properties within a certain period of time, that is, to meet the compressive strength and bonding strength indicators. Here, based on the anti-permeability test, the fly ash content is 15%. Sulphoaluminate cement and ordinary silicate cement are compounded and the setting time test is carried out. The test results are as follows: Figure 2 shown.
[0044] from Figure 2It can be seen that with the increase of sulphoaluminate cement content, the setting time of the mortar system shortens rapidly. When the sulphoaluminate cement content ranges from 5% to 15%, the setting time of the system drops sharply; when the sulphoaluminate cement content is between 20% and 60%, the setting time of the system decreases slowly. When the sulphoaluminate cement content in the system is slightly less than 0, the setting time of the system is slightly longer than that of the pure silicate cement system. This is because the system contains 15% fly ash, and the hydration activity of fly ash is lower than that of cement, which leads to its prolonged setting time. When sulphoaluminate cement is added, the setting time of the system shortens rapidly. The main mineral components of sulphoaluminate cement are anhydrous calcium sulphoaluminate and dicalcium silicate, and its main hydration products are hydrated calcium sulphoaluminate and aluminum hydroxide gel. The hydration degree of its C4A3S1d is about 76% of 28d. The reason for the rapid setting of sulphoaluminate cement may be that the clinker contains CA, C 12 A 7 , f-CaO or CaS minerals, and these substances are related to the low or high clinker calcination temperature and the calcination atmosphere.
[0045] Adhesion properties test:
[0046] The bonding strength of the repair material was tested in accordance with the "Test Code for Cement and Cement Concrete in Highway Engineering (JTGE30 T0511)".
[0047] One of the important properties of cement-based repair materials is to achieve strong bonding with existing structures. In order to improve the bonding properties of the repair material, based on the research on chloride ion penetration resistance and setting time, soluble glue powder was introduced into it. At this time, the fly ash content was 15% and the sulphoaluminate cement content was 15%. The results are as follows Figure 3 shown.
[0048] from Figure 3 It can be seen that with the increase of the amount of rubber powder added, the bonding strength of the specimen increases accordingly. When the amount of rubber powder is 1.5%, its bonding strength almost reaches the maximum value, increasing by 46% compared with the baseline; when the amount of rubber powder is 2.0% and 2.5%, its growth trend is gentle. Soluble rubber powder can be well dispersed in the repair material system, and has a ball effect, which can enhance the fluidity of the system, and dissolve into a transparent viscous substance, which can further improve the interface performance between the repair material and the existing structure.
[0049] Strength property test:
[0050] The compressive strength of the repair material was tested with reference to the "Test Method for Strength of Cement Mortar (GBT17671-1999)".
[0051] In order to improve the strength characteristics of the repair material, polypropylene fibers of different lengths and dosages were added to the repair material. At this time, the fly ash dosage was 15%, the sulphoaluminate cement base dosage was 15%, and the rubber powder dosage was 1.5%. The results are as follows Figure 4 shown.
[0052] from Figure 4 It can be seen that the length and dosage of polypropylene fibers have different degrees of influence on the strength of the specimens. In terms of polypropylene fiber length, 6mm has a more obvious improvement on the strength of the specimens. In particular, when the dosage is 0.15%, the 3d and 28d flexural strengths are increased by 21.4% and 33.3% respectively compared with the benchmark. After the fiber dosage exceeds 0.15%, the strength improvement is slow. Under the same conditions, the specimens with fiber lengths of 3mm and 9mm are 8% and 12% lower than those with 6mm (dosage 0.15%, 28d), respectively. The effect of fiber characteristics on the compressive strength of the specimens has similar characteristics. The bridging effect of fibers in cement-based materials improves their strength, and their multi-point cracking characteristics can further reduce the risk of damage to cement-based materials.
[0053] In summary, the physical and chemical effects of fly ash significantly improve the anti-permeability performance of the repair material; sulphoaluminate cement can accelerate the setting time of the repair material, which is helpful for the rapid repair of the existing damaged structure; the addition of glue powder forms a mucous membrane substance in the system, which helps to improve the bonding performance of the repair material; the appropriate type of polypropylene fiber can significantly improve the flexural strength and compressive strength of the repair material. Fly ash and sulphoaluminate cement base can improve the anti-permeability performance of the repair material and adjust the setting time; when the glue powder is added at 1.5%, the effect is better, and the bonding strength of the repair material is increased by 46%; when the 6mm polypropylene fiber is added at 0.15%, its 3d and 28d flexural strengths are increased by 21.4% and 33.3% respectively compared with the baseline.
[0054] The advantages and positive effects of the present invention are:
[0055] The present invention discloses a multi-component cement-based repair material, which uses silicate cement and fly ash as main repair materials, and can repair micro cracks in existing structures to a certain extent; polypropylene fiber can improve its crack resistance; on this basis, soluble rubber powder and epoxy resin are introduced to further improve the anti-seepage performance of the repair material. At the same time, sulfoaluminate cement and accelerator greatly reduce the setting time of cement-based materials, so that the comprehensive performance of defective structures can be quickly improved in a relatively short time. Adding silica ash to the silicate cement-based repair material improves the early strength and density of the repair material. The present invention discloses a method for preparing a multi-component cement-based repair material, which has simple steps, is easy to use, and is energy-saving and environmentally friendly.
[0056] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A multi-component cement-based repair material, characterized in that: The material includes the following components by mass percentage: silicate cement, fly ash content 0% to 30%, sulphoaluminate cement content 5% to 50%, rubber powder content 1% to 2.5%, polypropylene fiber content 0.1% to 0.25%; the benchmark mix ratio of the test piece is: cement: water: sand = 1:0.5:
1.
2. The multi-component cement-based repair material according to claim 1, characterized in that: The silicate cement is P·O42.5 silicate cement.
3. The multi-component cement-based repair material according to claim 1, characterized in that: The fly ash has an average particle size of 80 μm and comprises the following components by mass percentage: CaO 6.80%, SiO2 46.50%, Al2O3 33.80%, Fe2O3 9.80%, MgO 0.70%, SO3 0.80%, K2O 0.60%, Na2O 0.10%, and LOI 0.90%.
4. The multi-component cement-based repair material according to claim 1, characterized in that: The tensile strength of the polypropylene fiber is 385 MPa, the length range is 6 mm to 12 mm, and the elastic modulus is 5.8 GPa.
5. The multi-component cement-based repair material according to claim 1, characterized in that: The sulphoaluminate cement is SAC42.5 rapid hardening sulphoaluminate with a 1d strength of 31 MPa and a 3d strength of 45.5 MPa.
6. The multi-component cement-based repair material according to claim 1, characterized in that: The rubber powder is a dispersible or soluble rubber powder, and its composition is ethylene-vinyl acetate polymer (EVA), with a glass transition temperature of 15°C and a bulk density of 550kg / m 3 , fineness 160μm.
7. The multi-component cement-based repair material according to claim 1, characterized in that: The sand is river sand with a fineness modulus of 2.
1.
8. A method for preparing the multi-component cement-based repair material according to claim 1, characterized in that: Put the silicate cement, fly ash, sulphoaluminate cement, rubber powder and polypropylene fiber weighed according to the ratio into the mortar mixing pot and pre-mix them evenly for 60 seconds. Then slowly add the tap water mixed with superplasticizer into the mixing pot and stir slowly for 60 seconds, stir quickly for 90 seconds, stir slowly for 60 seconds, and stir with a spatula. After stirring, the repair material is tested for material properties and the specimens are repaired.